The correlation between ocular residual astigmatism and wavefront-guided FS-LASIK correction effects in myopic astigmatism patients - Qingyun Zuo; Yu Zhang; Ming He; Siyi Wang; ZhiYu Du (Scientific Reports)
Abstract To evaluate the impact of ocular residual astigmatism (ORA) on the astigmatic correction outcomes of wavefront-guided femtosecond laser-assisted in situ keratomileusis (WFG FS-LASIK) in myopic astigmatism patients. Retrospective cohort study. This study analyzed 90 patients (177 eyes) undergoing WFG FS-LASIK at Chongqing Medal Eye Institute between January 2015 and May 2021, all with complete follow-up data spanning 15 days–6 months postoperatively. Participants were categorized into three groups based on the ratio of ORA to refractive astigmatism (RA), and the axial difference between ORA and anterior corneal astigmatism (ACA): Group1 (42 eyes): |ORA|/|RA| < 1 and the axial difference between ORA and ACA was ≦ 45°. Group 2 (86 eyes): |ORA|/|RA| < 1 and the axial difference between ORA and ACA was > 45°. Group3 (49 eyes): |ORA|/|RA| > 1 and the axial difference between ORA and ACA was > 45°. Uncorrected distance visual acuity (UDVA) at 6 months postoperatively was compared among the three groups. Alpins vector analysis was performed to compare the accuracy of astigmatic correction, quantified by: Angle of error (AE): axial deviation between the surgically induced astigmatism (SIA) and target induced astigmatism (TIA); Correction index (CI): ratio of SIA to TIA (ideal value = 1.0). The mean |AE| values significantly differed among groups (P < 0.05), being lowest in Group 1 (9.29°) and highest in Group 3 (26.64°). Correction index (CI) defined as the ratio of SIA to TIA. The mean CI values were1.00 (Group 1), 1.19 (Group 2) and 3.26 (Group 3).No statistically significant differences were observed in postoperative UDVA among the three groups (P > 0.05). In WGF FS-LASIK, the consistency between the axis of ORA and ACA affects the degree of deviation in astigmatic axis correction, but had no significant impact on UDVA.